2017
DOI: 10.1002/cbdv.201700295
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, and Molecular Docking Studies of Novel 4‐[4‐Arylpyridin‐1(4H)‐yl]benzoic Acid Derivatives as Anti‐HIV‐1 Agents

Abstract: The structural similarities between N1 substituted 1,4-dihydropyridines and the known gp41 inhibitors, NB-2 and NB-64, were considered in the current research for the design of some novel anti-HIV-1 agents. A series of novel 4-[4-arylpyridin-1(4H)-yl]benzoic acid derivatives were synthesized and after a comprehensive structural elucidation were screened for in vitro anti-HIV-1 activity. Most of the tested compounds displayed moderate to good inhibitory activity against HIV-1 growth and were evaluated for in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The authors believed that the presence of 2‐furyl and 2‐thienyl hetero‐aromatic substituents at the C4 position of 1,4‐dihydropyridine helps improve the anti‐HIV‐1 activity and decrease the cytotoxic effect on MT‐2 cell line. Docking studies performed in this report showed good electrostatic and hydrophobic interactions with the gp41 binding site …”
Section: Hiv‐1 Entry Inhibitorssupporting
confidence: 53%
See 1 more Smart Citation
“…The authors believed that the presence of 2‐furyl and 2‐thienyl hetero‐aromatic substituents at the C4 position of 1,4‐dihydropyridine helps improve the anti‐HIV‐1 activity and decrease the cytotoxic effect on MT‐2 cell line. Docking studies performed in this report showed good electrostatic and hydrophobic interactions with the gp41 binding site …”
Section: Hiv‐1 Entry Inhibitorssupporting
confidence: 53%
“…[ ][ ] HIV‐1 entrance inhibitors are potentially more precious among anti‐HIV medications, because these kinds of compounds can prevent transmission of HIV‐1 among individuals and can be used for prophylaxis. A variety of small molecules and peptides with different mechanisms of action have been investigated for their HIV‐1 entry inhibitory activity, among them Enfuvirtide (Fuzeon, also known as T20) and Maraviroc (MVP) are approved by FDA . Enfuvirtide an HIV‐1 CHR‐peptide‐based compound is the first HIV‐1 entry inhibitor that was approved as a drug in 2003 by FDA.…”
Section: Introductionmentioning
confidence: 99%
“…THPMs are provided through a Biginelli reaction including ethyl acetoacetate, aryl aldehyde, and urea. [9] Cytosine, thymine, and uracil, three important bases in nucleic acids, are pyrimidine derivatives and cytosine is existing in both RNA and DNA. [10,11] Newly, various THPMs were described to reveal antiurease activity (Figure 1).…”
mentioning
confidence: 99%
“…Compounds 4b and 4i showed poor activity against MCF-7 cell line. It should be noted that similar compounds with ethylester moiety at C-5 position were also reported as weak cytotoxic compounds against MCF-7 cell line (34).…”
Section: Discussionmentioning
confidence: 91%
“…When transfection was complete, 800 μL of the complete medium containing the synthesized compounds was added to the cells. The culture medium containing the virus was collected 48 h after transfection and the amount of the purified virus was measured using p24 ELISA assay kit (Cell Biolabs, France) (34).…”
Section: Methodsmentioning
confidence: 99%